THE INFLUENCE OF PERCEPTIONS OF THE USE OF VIDEO MEDIA ON STUDENTS' LEARNING INDEPENDENCE IN THE CLASS XI PAI SUBJECT OF SMA NEGERI 6 SINJAI - Munawaroh, Munawaroh; Ismail, Muh. Ilyas; Ista, Akbar (Universitas Islam Negeri Alauddin Makassar, 2024)
This research discusses the influence of perceptions of using video media on students' learning independence in Class XI PAI subjects at Sinjai State High School. This research uses a quantitative type of research method ex-post facto. Respondents in this study totaled 61 people who were obtained using Proporsional cluster random sampling, to collect data using a questionnaire instrument which was analyzed using descriptive and inferential statistics. The results of research using SPSS 24 obtained analysis results = 216 dan P-value= 000/2= 0 < 0,05, this means that Ho is rejected and Ha is accepted. Thus, it can be concluded that